1954
DOI: 10.2136/sssaj1954.03615995001800040001x
|View full text |Cite
|
Sign up to set email alerts
|

The Movement of Soil Moisture in Response to Temperature Gradients

Abstract: Using an air gap technique, it has been shown that the flow of moisture in the soil from warm to cool regions might occur largely in the vapor phase. This is accompanied by a return flow of liquid water in response to an induced flow potential gradient. The use of wire screens to make air gaps interferes with this process. The measured diffusion coefficient for vapor flow was higher than had been expected from diffusion data, but was substantially in agreement with that of other workers. The reasons for this h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
1

Year Published

1959
1959
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 0 publications
0
37
0
1
Order By: Relevance
“…A moisture content gradient is therefore set up in the direction of cold to hot, and liquid moisture may be returned to the hot side by capillary forces. Under steady-state conditions, a dynamic equilibrium exists between the two opposing processes, and the moisture is no longer uniformly distributed in the material (4,7,9).…”
Section: Discussion the Other So That The Heat Flows In The Verticalmentioning
confidence: 99%
See 1 more Smart Citation
“…A moisture content gradient is therefore set up in the direction of cold to hot, and liquid moisture may be returned to the hot side by capillary forces. Under steady-state conditions, a dynamic equilibrium exists between the two opposing processes, and the moisture is no longer uniformly distributed in the material (4,7,9).…”
Section: Discussion the Other So That The Heat Flows In The Verticalmentioning
confidence: 99%
“…2), the average ~noisture content in the test region is seen to be less than 2 per cent. Under the action of a temperature gradient, moisture moves from hot to cool regions (4,7,9). Thus the nloisture content at the cold side probably attained a value large enough to permit gravity drainage out of the test region, leaving an average moisture content in the test region of approximately 1.5 per cent.…”
mentioning
confidence: 99%
“…The water vapour flux under thermal gradients is an important part of water flow in soil. Philip and De Vries [11] also added a mechanistic enhancement factor () into the equation of thermally induced water vapour flow to consider the discrepancy between the predicted transfers using Fick's law and the measured water fluxes [12,13]. Despite the importance of  in modelling of coupled heat and moisture flow, few works have been focused on evaluating it experimentally and quantitatively [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Early pioneering studies, including Taylor and Cavazza (1954), Rollins et al (1954), Kuzmak and Sereda (1957), and Matthes and Bowen (1963), have demonstrated that moisture movement in response to a thermal gradient through an unsaturated soil occurs mainly in the vapor phase. In fact, experimentally observed values for water vapor diffusion under thermal gradients are several times higher than those predicted by a simple diffusion equation (Philip and DeVries 1957).…”
Section: Introductionmentioning
confidence: 99%